Addition Effect of Super Red Dragon Fruit Peel Extract on Dry Noodle Product - Wahyuni, Rekna; Nugroho, Matheus (Jurnal Teknologi Pertanian, 2014)
Super red dragon fruit peels extract (Hylocereus costaricensis) can be used to increase the macro-nutrients of dry noodles food consumption were more variable for the wider community and encourage the diversification of business people as well as meeting the needs of macro nutrients. Based on this background, it was required to investigate the effect of dragon fruit peel extract introduction dry noodles production in terms of levels of DPPH and consumers acceptance. The purpose of this study was to determine the addition effect of super red dragon fruit peels extract (Hylocereuscostaricensis) for DPPH and consumer acceptance of dry noodles. The experimental design used was the single randomized design (SRD). The data analysis was done as ANOVA with confidence interval of 5% and 1%. If significance is detectted, further data analysis is continued by LSD. For organoleptic test using Friedman test. The best treatment using the modified method of de GarmoSusrini.The conclusion of this study was that the addition of super red dragon fruit peels extract (Hylocereuscostaricensis) very significant effect on DPPH and consumer acceptance of dry noodles. The best treatment was the addition of super red dragon fruit peels extract of 20 ml with the following characteristics: moisture content of 4.567%; intensity of the red color (a +) 18.133; antioxidant (DPPH) 2.348%, ash content of 1.904%, the protein content of 14.661%, and the average of panelist preference level for color4.70; flavor 4.80; aroma 4.30; texture 4.90 which was between like and really like.Keywords: Antioxidan, DPPH, dragon fruit peel, dry noodle